Nouvelles raisons d'agir des acteurs de la pêche et de l'agriculture - Merri, Maryvonne; Képhaliacos , Charilaos (éditions Quae, 2016)
Faced with advancing technology and their entitlement to exploit this living resource, farmers and fishermen are questioning their very livelihood and how to change it. This book examines elements contributing to the reasons to take action: debates on renewable resources, decisions regarding their profession and its transmission to new generations, new division of labor.